2004
DOI: 10.1136/ard.2004.022152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide on mitochondrial respiratory activity of human articular chondrocytes

Abstract: Objective: To investigate the effect of nitric oxide (NO) on mitochondrial activity and its relation with the apoptosis of human articular chondrocytes. Materials and methods: Mitochondrial function was evaluated by analysing respiratory chain enzyme complexes, citrate synthase (CS) activities, and mitochondrial membrane potential (Dym). The activities of the mitochondrial respiratory chain (MRC) complexes (complex I: NADH CoQ 1 reductase, complex II: succinate dehydrogenase, complex III: ubiquinol cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 39 publications
4
125
1
1
Order By: Relevance
“…We recently demonstrated that OA chondrocytes, as compared with normal chondrocytes, display a significant decrease in activity of the MRC complexes II and III and a reduction in mitochondrial membrane potential (10). We also found that various key mediators involved in the pathogenesis of OA, such as the cytokines TNF␣ and IL-1␤ or the reactive nitrogen intermediate nitric oxide (NO), modulate the activity of different complexes of the MRC in cultured chondrocytes (24,25). However, the activity of the MRC is low in articular chondrocytes, due to the absence of vascularization and a hypoxic environment, as compared with that in vascularized tissue, and most of the ATP molecules arise from the glycolysis pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently demonstrated that OA chondrocytes, as compared with normal chondrocytes, display a significant decrease in activity of the MRC complexes II and III and a reduction in mitochondrial membrane potential (10). We also found that various key mediators involved in the pathogenesis of OA, such as the cytokines TNF␣ and IL-1␤ or the reactive nitrogen intermediate nitric oxide (NO), modulate the activity of different complexes of the MRC in cultured chondrocytes (24,25). However, the activity of the MRC is low in articular chondrocytes, due to the absence of vascularization and a hypoxic environment, as compared with that in vascularized tissue, and most of the ATP molecules arise from the glycolysis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the effect of mitochondrial dysfunction on COX-2 protein expression and PGE 2 synthesis, normal human chondrocytes were treated with several concentrations of different inhibitors of mitochondrial respiration commonly utilized to induce inhibition of the MRC. We selected rotenone, NPA, antimycin A, sodium azide, and oligomycin as inhibitors of complexes I, II, III, IV, and V, respectively (10,11,(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive production of oxidants such as NO may occur due to the IL-1β-induced expression of iNOS (43)(44)(45). In addition, IL-1β stimulates COX-2 expression to increase synthesis of PGE2, which is responsible for joint pain in KOA (46,47).…”
Section: Discussionmentioning
confidence: 99%